A low-stress self-supporting metal film filter and its preparation method

By adopting a self-supported multi-layer film structure without substrate and periodic stacking structure in metal film filters, the material ratio is optimized to reduce film stress, which solves the damage caused by stress during the existing filter during the preparation process, and improves the success of preparation rate and optical properties.

CN115074688BActive Publication Date: 2025-02-11SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210837040.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2025-02-11
Estimated Expiration
2042-07-15

AI Technical Summary

Technical Problem

During the preparation process, existing metal film filters are prone to breakage due to stress, resulting in spalling, falling off and substrate deformation, affecting yield and transmittance.

Method used

The self-supported multi-layer film structure without a substrate is adopted, and the proportion of two materials in each cycle is optimized through the periodic stacking structure, which reduces the overall stress of the film and improves the preparation success rate.

Benefits of technology

It significantly reduces the overall stress of the filter, reduces the generation of sand holes, and improves the yield and optical properties of self-supported metal film filters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115074688B_ABST
    Figure CN115074688B_ABST
Patent Text Reader

Abstract

A low-stress self-supporting metal thin film filter and a preparation method thereof, wherein the film system structure of the thin film filter is: B / [A / B]^n or A / B / [A / B]^(n-1) / A, wherein A represents the main layer material, which has a weak absorption characteristic in the transmission band of the filter, B represents the auxiliary layer material, n represents the number of cycles of the periodic structure [A / B], and the periodic thickness of the periodic structure is D, D=d A +d B , where d A is the film thickness of the main layer material A, d B The ratio of the thickness of the auxiliary layer material B to the thickness of the main layer material A in each cycle to the cycle thickness D is in the range of 0.5-0.99. Compared with the single-layer membrane filter and the sandwich structure filter, the comprehensive stress of the film is reduced by 50-80%, the number of micron-sized sand holes is reduced by 3-5 times, and it is not easy to be damaged during the demolding process, so that the preparation success rate of the self-supporting metal film filter is increased by 25-75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of precision optical elements, and in particular relates to a low-stress self-supporting structure metal film filter and a preparation method thereof. Background Art

[0002] The spectral composition of a light source of a specific wavelength will change before and after it is absorbed by the ultra-thin metal film, and the filter is made of this ultra-thin metal film. The filter is an optical element used to select the required band. It selects the band by reflecting or absorbing certain bands of the incident light and transmitting other bands.

[0003] Magnetron sputtering deposition is a common process for preparing metal thin film filters. Sputtering coating is to bombard the target surface with energetic particles in a near-vacuum condition, so that the bombarded target particles are deposited on the substrate to form a thin film. The deposition rate of sputtering coating is usually relatively stable, and the film thickness is easy to control. By adjusting the deposition time, multilayer films with nanometer-level thickness can be prepared. However, self-supporting filter discs are usually easy to break, especially under stress, they are prone to wrinkles and cracks.

[0004] The process flow of self-supporting filter discs is as follows: a thin film is plated on an etchable or soluble substrate (such as some ionic crystals including NaCl) by magnetron sputtering, and then the substrate is dissolved. The filter disc with this structure is simple to make, but the prepared filter disc is very fragile. There is usually a large stress in the nanofilm, which has an adverse effect on the performance of the filter disc, especially the yield rate during the preparation process. When the film stress is severe, it will directly cause the filter disc to spall and fall off, causing the filter disc to be damaged. Sometimes the stress will also affect the substrate to a certain extent, causing the substrate to deform. The stress in the filter disc mainly comes from thermal stress and internal stress. Thermal stress is mainly caused by the difference in thermal expansion coefficients between the film and the substrate material; internal stress mainly depends on factors such as the microstructure and defects of the film. For example, an increase in the density of the film may lead to an increase in its compressive stress.

[0005] Single-layer and multi-layer metal film filters usually show significant compressive stress, and the higher the density of the filter, the greater the compressive stress in the film. Therefore, filters prepared by sputtering usually show stronger compressive stress. There are many ways to adjust the filter stress. Generally, by optimizing the substrate and film materials, adjusting the deposition technology, deposition conditions, and post-processing, the purpose of adjusting the filter stress can be achieved to a certain extent.

[0006] The US patent application US20060087739A1 of JDS Uniphase of the United States discloses a filter for visible light-near infrared band, which includes a multi-layer thin film, a substrate, and a compensation layer designed between the substrate and the film layer; the preferred material for the compensation layer is ZrO2, and the total stress of the filter is adjusted by adjusting the structure of the compensation layer. However, this filter structure is not suitable for short-wave band fields such as extreme ultraviolet and soft X-rays. The main reason is that the increase in the overall thickness of the film caused by this complex structure, as well as the addition of substrate and compensation layer materials, will seriously reduce the overall transmittance and filtering efficiency of the filter in the short-wave band.

[0007] The paper by Bibishkin et al. (Bibishkin MS, Chkhalo NI, Gusev SA, et al. Multilayer Zr / Si filters for EUV lithography and for radiation source metrology [J]. Proc. of SPIE, 2008, 7025) describes a multilayer Zr / Si structure filter supported by a grid substrate or self-supported. This structure is mainly used to enhance the mechanical strength of the filter against damage in its subsequent application scenarios. No method is proposed to adjust stress during the filter preparation process to improve the filter preparation yield.

[0008] Different from the above two reported methods, the present invention proposes a substrate-free self-supporting multilayer membrane filter structure: no additional materials that affect the transmittance are added, the total thickness of the film and the total thickness of each film layer material are not changed, and an improved and relatively simple periodic stacking structure is adopted to optimize the ratio of the two materials in each period; the main purpose of this structure is to significantly reduce the film comprehensive stress of the filter during the film forming and film stripping preparation process, so as to improve the success rate of self-supporting thin film filter preparation and reduce the formation of sand holes. Compared with the multilayer structure reported previously, the multilayer membrane periodic structure proposed by the present invention has a larger thickness difference between the two different materials and a larger range of material thickness combinations. It can perform more accurate and effective stress adjustment for metal thin film filters with different stress properties, so as to significantly improve the yield of self-supporting thin film filter preparation. Summary of the invention

[0009] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a low-stress self-supporting structure metal film filter and a preparation method thereof. On the basis of a single-layer membrane filter and a sandwich structure filter, no additional materials that affect the transmittance are added, and the total thickness of the film and the total thickness of each film layer material are not changed. By adopting an optimized structure of a periodic arrangement structure and preparing it by a demolding method, a self-supporting multilayer metal film filter with lower comprehensive stress, fewer sand holes, and higher yield is obtained. Compared with single-layer membrane and sandwich structure filters, the comprehensive stress is reduced by 50-80%, the number of sand holes is reduced by 3-5 times, and the preparation success rate is increased by 25-75%.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] On the one hand, the present invention provides a low-stress self-supporting metal film filter, which is characterized in that the film system structure is: B / [A / B]^n or A / B / [A / B]^(n-1) / A, wherein A represents the main layer material, which has a weak absorption characteristic in the transmission band of the filter, and B represents the auxiliary layer material, which generally plays an auxiliary role such as protection and spacing, and has no restrictions on its absorption characteristics in the transmission band of the filter. n represents the number of cycles of the periodic structure [A / B], and the period thickness of the periodic structure is D, D=d A +d B , where d A is the film thickness of the main layer material A, d B is the film thickness of the auxiliary layer material B, and the ratio Γ of the film thickness of the main layer material A in each period to the period thickness D is in the range of 0.5-0.99.

[0012] Preferably, the stress characteristics of the auxiliary layer material B are complementary to the stress characteristics of the main layer material A, and the auxiliary layer material B can compensate and adjust the comprehensive stress of the filter.

[0013] Preferably, the film layer materials A and B are selected from two materials selected from B4C, Si, Mg, Al, Fe, Ni, Zn, Zr, Sc, Nb, Mo, and Cu according to specific needs.

[0014] Preferably, the range of n is 2-699, and the optimal period value depends on the characteristics of the material combination.

[0015] Preferably, the total thickness of the film ranges from tens to hundreds of nanometers, and can even reach micrometer level.

[0016] On the other hand, the present invention also provides a method for preparing a low-stress self-supporting metal film filter, which is characterized in that the method comprises the following steps:

[0017] Step (1) depositing materials A and B on the surface of a soluble substrate by magnetron sputtering to form a film structure B / [A / B]^n or A / B / [A / B]^(n-1) / A;

[0018] Step (2) performing a film stripping treatment on the film obtained in step (1);

[0019] Step (3) fixes the film after demolding obtained in step (2) using a soft contact mounting ring.

[0020] The step (1) specifically comprises:

[0021] 1.1 Magnetron sputtering coating equipment is used for deposition. The soluble NaCl substrate, target A and target B are placed in the vacuum coating chamber, and the background vacuum is pumped to better than 2.0×10 -4 Pa;

[0022] 1.2 Set the coating parameters. Depending on the sputtering material, the sputtering power density range is 2-5W / cm 2 , the working gas is high purity Ar gas;

[0023] 1.3 Start the revolution (the sample plate can rotate at the same time) and start the coating process until the coating is completed.

[0024] The step (2) specifically comprises:

[0025] 2.1 Inject deionized water into the culture dish;

[0026] 2.2 Slowly place the NaCl substrate coated with the film into the culture dish at an angle of 30°-60° to the horizontal plane;

[0027] 2.3 After the film is separated from the substrate, remove the substrate first, let the unsupported film stand in the culture dish for 100 seconds to 300 seconds, and then remove it.

[0028] Preferably, the soft-contact mounting ring described in step (3) is made of polytetrafluoroethylene. The mounting ring is bonded to the upper surface of the film through epoxy resin, thereby fixing the metal film after demolding.

[0029] The low stress characteristics are obtained by measuring the surface shape change before and after coating with a white light interferometer and calculating with the Stoney formula. At the same time, a self-built laser sand hole detection device is used to characterize the prepared filter.

[0030] Preferably, the soluble NaCl substrate is purchased from Shanghai Hengyi Optical Precision Machinery Co., Ltd., and is a round substrate with a diameter of 15 mm and a thickness of 2 mm.

[0031] Preferably, during the de-membrane process of the filter disc, the rate of injecting deionized water is 50-100 ml / min. After the film is separated from the substrate, it is fixed by a mounting ring made of polytetrafluoroethylene. The mounting ring is fixed to the upper surface of the film through epoxy resin to play an auxiliary support role. The fixing process keeps the film as flat as possible. The diameter of the filter disc is 25 mm.

[0032] Preferably, in the sand hole detection step, the self-built laser sand hole detection device is composed of a helium-neon laser, a diffraction optical path, a CCD receiver and a computer. The number of sand holes in the filter is calculated by a graphics processing software. The minimum resolution of sand holes is 5 μm.

[0033] Compared with the prior art, the beneficial effects of the present invention are:

[0034] 1) Compared with single-layer membrane filters and sandwich structure filters, the comprehensive stress of the film of the present invention is reduced by 50-80%, and the number of sand holes of micron size is reduced by 3-5 times.

[0035] 2) The present invention improves the film-forming preparation process of the self-supporting film and effectively enhances the comprehensive performance of the self-supporting metal film filter.

[0036] 3) Compared with single-layer membrane filters and sandwich structure filters, the periodic multilayer membrane filter prepared by the present invention is less likely to be damaged during the demolding process, which increases the success rate of preparing self-supporting metal thin film filters by 25-75%, providing a new idea for the large-scale and high-yield preparation of self-supporting filters. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic structural diagram of the low stress self-supporting metal film filter of the present invention.

[0038] Figure 2 The following are comparison diagrams of the holes in the Zr / Si self-supporting metal thin film filter disc characterized by using a hole detection device. (a) is the hole condition of the pure Zr single-layer membrane filter disc with a conventional structure, and (b) is the hole condition of the Zr / Si self-supporting multilayer membrane filter disc with a use cycle of 10 according to the embodiment of the present invention.

[0039] Figure 3 The following are comparison diagrams of the sand holes of the Al / Fe self-supporting metal thin film filter disc characterized by using a sand hole detection device. Among them, (a) is the sand hole situation of the Al / Fe double-layer membrane structure filter disc, (b) is the sand hole situation of the Al / Fe self-supporting multilayer membrane filter disc with a period of 5 used in the embodiment of the present invention, and (c) is the sand hole situation of the Al / Fe self-supporting multilayer membrane filter disc with a period of 10 used in the embodiment of the present invention.

[0040] Figure 4The stress evolution and demolding success rate statistics of Zr / Si self-supporting metal thin film filters with different structures, including conventional pure Zr single-layer membrane filters, Si / Zr / Si sandwich structure filters, and Zr / Si self-supporting multilayer membrane filters with a period of 10 used in the embodiment of the present invention.

[0041] Figure 5 The stress evolution and demolding success rate statistics of Al / Fe self-supporting metal thin film filters with different structures are shown in the figure, including Al / Fe double-layer membrane structure filter, Al / Fe self-supporting multi-layer membrane filter with a period of 5 used in the embodiment of the present invention, and Al / Fe self-supporting multi-layer membrane filter with a period of 10 used in the embodiment of the present invention. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with embodiments and drawings.

[0043] Please refer to Figure 1 , Figure 1 It is a structural schematic diagram of the low stress self-supporting metal film filter of the present invention. As can be seen from the figure, a low stress self-supporting metal film filter, the film system structure is: B / [A / B]^n or A / B / [A / B]^(n-1) / A, wherein A represents the main layer material, which has a weak absorption characteristic in the transmission band of the working filter, B represents the auxiliary layer material, which generally plays an auxiliary role such as protection and spacing, and has no restrictions on its absorption characteristics in the transmission band of the working filter, n represents the number of cycles of the periodic structure [A / B], and the period thickness of the periodic structure is D, D=d A +d B , where d A is the film thickness of the main layer material A, d B is the film thickness of the auxiliary layer material B, and the ratio Γ of the film thickness of the main layer material A in each period to the period thickness D is in the range of 0.5-0.99.

[0044] Example 1: Preparation and detection of Zr / Si metal thin film filter with a period of 10.

[0045] Taking the preparation and detection of a Zr / Si metal film filter with a period of 10 as an example, the optimized structure of the low-stress self-supporting metal film filter proposed by the present invention is explained. The method comprises the following steps:

[0046] Determine the Zr single layer film and Si / Zr / Si sandwich structure film: prepare a Zr single layer film with a thickness of 300nm, and a Si / Zr / Si sandwich film with a structure of 11nm Si / 300nm Zr / 11nm Si respectively.

[0047] Characterization of basic stress: The surface shape of Zr single-layer film and Si / Zr / Si sandwich structure film was characterized respectively. The curvature degree (P) of the substrate surface of the film was characterized before and after coating, and the change value ΔP before and after can be substituted into the Stoney formula to calculate the comprehensive stress of the film. The results are shown in Table 1. The stress of Zr single-layer film is -0.358GPa, and the stress of Si / Zr / Si sandwich structure film is 0.347GPa. After adding the auxiliary layer, the stress sign of the sandwich structure film changes, but the absolute value of the comprehensive stress is still at a very high level (0.347GPa), and the success rate of its demolding is 0.

[0048] Periodic structure optimization: Without changing the total thickness of the sandwich structure film and maintaining the total thickness of each film layer material, a Zr / Si multilayer film with a period of 10 was designed for plating. Its structure and thickness can be expressed as: 2nm Si / [30nm Zr / 2nm Si]^10. The stress characterization results of the periodic multilayer film are shown in Table 1. The stress of the multilayer film prepared with a periodic structure is greatly reduced, here reduced to only 0.091GPa.

[0049] Table 1

[0050] Film structure: Zr Si / Zr / Si Zr / Si N=10 Stress(GPa): -0.358 0.347 0.091

[0051] Filter stripping: The NaCl substrate is dissolved, and the self-supporting film is fixed on the mounting ring to prepare a self-supporting film filter. Films with large stress are easily damaged during the stripping process. The statistical results of the success rate of stripping of the three structural films are as follows Figure 4 The success rate of preparing Zr single-layer membrane filter is 2 / 4 (50%), the success rate of preparing Si / Zr / Si sandwich structure filter is 0 / 4 (0%), and the success rate of preparing Zr / Si multilayer membrane filter with a period of 10 is 4 / 4 (100%).

[0052] Sand hole characterization: The successfully prepared filter is fixed on the laser sand hole detection device for characterization. Figure 2 This is a comparison of the pinholes in the Zr / Si self-supporting metal film filter. The Si / Zr / Si sandwich structure filter is completely damaged and cannot be characterized. Figure 2 It can be seen that the number of sand holes in the Zr single-layer membrane filter a is 1, and the diameter size is in the micron order; the number of sand holes in the Zr / Si multi-layer membrane filter b with a period of 10 is 0.

[0053] Example 2: Preparation and detection of Al / Fe metal film filter with a period of 5.

[0054] Taking the preparation and detection of an Al / Fe metal thin film filter with a period of 5 as an example, the optimized structure of the low-stress self-supporting metal thin film filter proposed by the present invention is explained. The method comprises the following steps:

[0055] Determine the Al / Fe double-layer film structure: Prepare an Al / Fe double-layer film with a structure of 200nm Al / 20nm Fe. Due to the special requirements of the project, the preparation of a sandwich structure film was not carried out here.

[0056] Characterization of basic stress: The Al / Fe double-layer structure film was characterized in terms of surface shape. The curvature (P) of the substrate surface of the film was characterized before and after coating. The change value ΔP before and after can be substituted into the Stoney formula to calculate the film's comprehensive stress. The results are shown in Table 2. The stress of the Al / Fe double-layer film is -0.273 GPa. The stress of the double-layer structure film is a large value, and its success rate of film stripping is low.

[0057] Periodic structure optimization: Without changing the total thickness of the double-layer structure film and maintaining the total thickness of each film layer material, an Al / Fe multilayer film with a period of 5 is first designed for plating, and its structure and thickness can be expressed as: 20nm Al / 4nm Fe / [40nm Al / 4nm Fe]^4 / 20nm Al; then an Al / Fe multilayer film with a period of 10 is designed for plating, and its structure and thickness can be expressed as: 10nm Al / 2nm Fe / [20nm Al / 2nm Fe]^9 / 10nm Al. The stress characterization of the two periodic multilayer films is shown in Table 2 below: Compared with the double-layer structure film, the stress sign of the multilayer film prepared with a 5-period structure changes, and the absolute value of the stress decreases significantly, only 0.038GPa; while the absolute value of the stress of the multilayer film prepared with a 10-period structure is still large, at 0.145GPa.

[0058] Table 2

[0059] Film structure: Al / Fe Al / Fe N=5 Al / FeN=10 Stress(GPa): -0.273 0.038 0.145

[0060] Filter stripping: The NaCl substrate is dissolved, and the self-supporting film is fixed on the mounting ring to prepare a self-supporting film filter. Films with large stress are easily damaged during the stripping process. The success rate of stripping of the three structural films is statistically shown as follows Figure 5 : The preparation success rate of Al / Fe double-layer thin film filter is 1 / 4 (25%), the preparation success rate of Al / Fe multi-layer membrane filter with a period of 5 is 4 / 4 (100%), and the preparation success rate of Al / Fe multi-layer membrane filter with a period of 10 is 2 / 4 (50%).

[0061] Sand hole characterization: The successfully prepared filter is fixed on the laser sand hole detection device for characterization. Figure 3 This is a comparison of the pinholes of the Al / Fe self-supporting metal film filter. The pinholes of the Al / Fe double-layer film filter a are clearly distributed and the number is large. Figure 3It can be seen that the number of sand holes in the Al / Fe multilayer membrane filter b with a period of 5 is 3, and the diameter size is in the micron order; the number of sand holes in the Al / Fe multilayer membrane filter c with a period of 10 is 5, and the diameter size is in the micron order. The experiment shows that the Al / Fe multilayer membrane filter with a period of 5 has lower comprehensive stress, higher preparation success rate, and better sand hole suppression.

[0062] Experiments have shown that, as described in the present invention, when preparing a self-supporting metal film filter, optimizing the periodic structure can significantly reduce the comprehensive stress of the film, improve the success rate of self-supporting film preparation, and reduce the formation of filter sand holes. For many film materials with large stress, the present invention can significantly improve many preparation process problems such as the decline in yield caused by stress, while reducing the formation of sand hole defects, thereby improving the optical performance of the self-supporting metal film filter.

Claims

1. A low stress self-supporting metal film filter, characterized in that: The film system structure is: B / [A / B]^n or A / B / [A / B]^(n-1) / A, wherein A represents the main layer material, which has weak absorption characteristics in the transmission band of the filter, B represents the auxiliary layer material, the film layer materials A and B are Zr and Si respectively, or the film layer materials A and B are Al and Fe respectively, n represents the number of cycles of the periodic structure [A / B], and the periodic thickness of the periodic structure is D, D=d A +d B , where d A is the film thickness of the main layer material A, d B is the film thickness of the auxiliary layer material B, the ratio Г of the film thickness of the main layer material A in each period to the period thickness D is in the range of 0.5-0.99; the total thickness of the film system structure is in the range of 220-322nm; The stress characteristics of the auxiliary layer material B are complementary to the stress characteristics of the main layer material A, and the auxiliary layer material B can compensate and adjust the comprehensive stress of the filter; The range of n is 2-699.

2. The low stress self-supporting metal thin film filter according to claim 1, characterized in that: Compared with single-layer membranes and sandwich structure filters, the membrane filter of the membrane system structure has a comprehensive stress reduction of 50-80% and a preparation success rate increase of 25-75%.

3. The low stress self-supporting metal thin film filter according to claim 1, characterized in that: The film structure is: 20nm Al / 4nm Fe / [40nm Al / 4nm Fe]^4 / 20nm Al.

4. A method for preparing a low-stress self-supporting metal thin film filter according to claim 1, characterized in that: The method comprises the following steps: Step (1) depositing materials A and B on the surface of a soluble substrate by magnetron sputtering to form a film structure B / [A / B]^n or A / B / [A / B]^(n-1) / A; Step (2) performing a film stripping treatment on the film obtained in step (1); Step (3) fixes the film after demolding obtained in step (2) with a soft contact mounting ring.

5. The method for preparing a low-stress self-supporting metal thin film filter according to claim 4, characterized in that: The step (1) specifically comprises: 1.1 Magnetron sputtering coating equipment is used for deposition. The soluble NaCl substrate, target A and target B are placed in the vacuum coating chamber, and the background vacuum is pumped to better than 2.0×10 -4 Pa; 1.2 Set the coating parameters. Depending on the sputtering material, the sputtering power density range is 2-5W / cm 2 , the working gas is high purity Ar gas; 1.3 Start the revolution (the sample plate can rotate at the same time) and start the coating process until the coating is completed.

6. The method for preparing a low-stress self-supporting metal thin film filter according to claim 4, characterized in that: The step (2) specifically includes: 2.1 Inject deionized water into the culture dish; 2.2 Slowly place the NaCl substrate coated with the film into the culture dish at an angle of 30°-60° to the horizontal plane; 2.3 After the film is separated from the substrate, remove the substrate first, let the unsupported film stand in the culture dish for 100 seconds to 300 seconds, and then remove it.

7. The method for preparing a low-stress self-supporting metal thin film filter according to claim 4, characterized in that: The soft-contact mounting ring described in step (3) is made of polytetrafluoroethylene. The mounting ring is bonded to the upper surface of the film through epoxy resin, thereby fixing the metal film after demolding.

8. A low stress self-supporting metal film filter according to any one of claims 1 to 3, characterized in that: The low stress characteristic is obtained by measuring the surface shape change before and after coating with a white light interferometer and calculating with the Stoney formula.

Citation Information

Patent Citations

  • Low net stress multilayer thin film optical filter

    US20060087739A1

  • Filter disc for X-ray and soft X-ray wave bands and preparation method thereof

    CN112820439A

  • Multi-layered optical filter film and production method thereof

    US5241417A